Are agroecological cooperative supermarkets an alternative for scaling sustainable food? - Sanz-Cañada, Javier; Yacamán-Ochoa, Carolina; Pérez-Campaña, Rocío (Frontiers in Sustainable Food Systems, 2024)
The paper attempts to investigate the capacity of agroecological cooperative supermarkets in Spain to promote scaling of food products by means of a double perspective. We first employ a vertical scaling approach to analyse the issues affecting the governance and collective organisation of the Cooperative Supermarket Network (CSN), set up in May 2022 and comprising eleven Spanish supermarkets. Secondly, we employ a perspective of horizontal scaling to investigate the potential for increased numbers of members, as well as the geographic and sociodemographic variables at play which limit the abovementioned scaling: to this end we employ the case study of the cooperative supermarket La Osa, opened in Madrid in December 2020. We adopt a methodology based on participatory action research throughout the years 2022 and 2023, in which the research team was involved in the real processes of creation and development of the CSN or of La Osa. The hypothesis refers to whether agroecological cooperative supermarkets constitute a formula for efficient retail distribution for scaling sustainable food in Spain: this, indeed, has proven to be the case. As opposed to the first-generation options for responsible consumption, these supermarkets appear to contribute to generating significant economies of scale and scope. In terms of vertical scaling, joint provision of services, as well as the gaining of political influence in society, constitute the main advantages in relation to the functioning of the CSN. While the recruitment of new members has heretofore been considered a priority in horizontal scaling, particular emphasis should also be placed on loyalty strategies targeting existing members.